2017
DOI: 10.1111/cch.12525
|View full text |Cite
|
Sign up to set email alerts
|

Which children and young people are excluded from school? Findings from a large British birth cohort study, the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: Exclusion from school was associated with child, family and school-related factors identifiable at, or prior to, primary school age. Child health professionals have an important role in the holistic, multidisciplinary assessment of children who are at risk of exclusion from school. Mental health and neurodevelopmental difficulties should be recognized and supported, to improve the health and educational outcomes among this vulnerable group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…Prospectively collected data at population level offer an opportunity to study temporal relationships between poor mental health and exclusion from school, but given that the latter is uncommon, sufficiently large data sets are rare. Several studies suggested a strong relationship between psychiatric disorder and exclusion from school (Bowman-Perrott et al, 2011;Ford et al, 2012;Paget et al, 2018;Parker et al, 2016Parker et al, , 2018Patton et al, 2014;Whear et al, 2013). Analyses of data from a nationally representative population sample suggested a bidirectional relationship between exclusion and poor mental health (Ford et al, 2018), indicating that effective intervention to support the learning and mental health of children who struggle with school could prevent both future mental disorders and exclusions (Beckett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Prospectively collected data at population level offer an opportunity to study temporal relationships between poor mental health and exclusion from school, but given that the latter is uncommon, sufficiently large data sets are rare. Several studies suggested a strong relationship between psychiatric disorder and exclusion from school (Bowman-Perrott et al, 2011;Ford et al, 2012;Paget et al, 2018;Parker et al, 2016Parker et al, , 2018Patton et al, 2014;Whear et al, 2013). Analyses of data from a nationally representative population sample suggested a bidirectional relationship between exclusion and poor mental health (Ford et al, 2018), indicating that effective intervention to support the learning and mental health of children who struggle with school could prevent both future mental disorders and exclusions (Beckett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The bad intention, sometimes with which students can use the internet and mobile phones, generates a new type of aggression called cyberbullying [3]. All these aspects of violence are beginning to be considered a major public health problem [4], specifically for children [5], sometimes generating adverse behavior [6] and even leading to suicidal behavior in young people [7].…”
Section: Introductionmentioning
confidence: 99%
“…An extreme issue concerns children's exclusion from school (House of Commons Education Committee, 2018). In this case, children with SEN are even more disadvantaged (Paget et al, 2018). Interestingly, the Warnock report mentioned exclusion only once, with respect to children with emotional and behavioral difficulties.…”
Section: Exclusionmentioning
confidence: 95%